Ethyl Gallate Isolated from Castanopsis cuspidata var. sieboldii Branches Inhibits Melanogenesis and Promotes Autophagy in B16F10 Cells - Moon-Hee Choi; Seung-Hwa Yang; Da-Song Kim; Nam-Doo Kim; Hyun-Jae Shin (MDPI AG, 2023)
The Castanopsis cuspidata var. sieboldii (CCS) plant grows predominantly in temperate regions of Asian countries, such as South Korea. Research on CCS has so far concentrated on the nutritional analysis, antioxidant activity, and anti-inflammation properties of its branches. However, the isolation of compounds and structural elucidation of effective single molecules remain unexplored, necessitating further exploration of CCS branches. Therefore, this study demonstrates the antioxidant and antimelanogenic activity of a single substance of ethyl gallate (EG) isolated from CCS branch extracts. Notably, the antimelanogenic (whitening) activity of EG extracted from CCS branches remains unexplored. Tyrosinase inhibition, kinetic enzyme assays, and molecular docking studies were conducted using mushroom tyrosinase in order to examine the antioxidant mechanism and antimelanin activity of EG in B16F10 melanoma cells. Nontoxic EG concentrations were found to be below 5 µg/mL. While EG significantly reduced the levels of whitening-associated proteins, p-CREB, and p-PKA, it dose-dependently inhibited the expression of TYR, TRP-1, TRP-2, and transcription factor (MITF). In addition, EG downregulated melanogenetic gene expression and activated autophagy signals. Therefore, EG extracted from CCS branches could serve as a novel functional cosmetic material with antimelanogenic and autophagy-enhancing activity.